Intermediate ions as indicator for local new particle formation - S. Tuovinen; J. Lampilahti; V.-M. Kerminen; M. Kulmala (Aerosol Research)
Atmospheric aerosol particles have a considerable influence on climate via both aerosol–radiation and aerosol–cloud interactions. A major fraction of global aerosol particles, in terms of their number concentration, is due to atmospheric new particle formation (NPF) that involves both neutral and charged clusters and particles. NPF is the major source of atmospheric intermediate ions, i.e., charged particles with mobility diameters between approx. 2 and 7 nm. We investigate ion concentrations between 1.7 and 3.1 nm at the SMEAR II (Station for Measuring Forest Ecosystem–Atmosphere Relations II) measurement station in Hyytiälä, Finland. Both negative and positive ion number size distributions measured by a Neutral cluster and Air Ion Spectrometer (NAIS) are used. Our aim is to find the best diameter size range of ions for identifying and evaluating the intensity of local intermediate ion formation (LIIF). Intermediate ion formation (IIF) refers to the formation of intermediate ions through NPF, while local means that the growth of such ions from smaller clusters has occurred in close proximity (e.g., within 500 m to 1 km) to the measurement site, i.e., locally. We find that the ions in the mobility diameter size range of 2.0–2.3 nm are the best suited for detection of LIIF. The ion concentrations in this size range indicate the elevated rates of IIF, and the potential distances the growing ions have traveled are smaller than those for larger ions. In addition, in Hyytiälä, the negative ion concentrations are more sensitive to IIF than the positive ion concentrations due to the higher difference in concentrations between periods of IIF and the background. Therefore, we recommend the concentrations of ions with diameters 2.0–2.3 nm as the best choice for identifying and evaluating the intensity of LIIF.